Patterns of caregivers' feeding practices and associated characteristics among preschool-age children in the United States. (1st January 2022) - Rahmaty, Zahra; Johantgen, Mary E.; Storr, Carla L.; Gilden, Robyn; Wang, Yan; Black, Maureen M.
Abstract: During early childhood, caregiver feeding practices (FP) influence children's diet and eating habits. Inconsistent methods of operationalizing FP have resulted in limited evidence regarding simultaneous FP patterns. This study examined the heterogeneity in FP among caregivers of preschoolers, along with the child, caregiver, and family characteristics associated with FP patterns. Caregivers of preschoolers (n = 437, 90% women) enrolled in 50 childcare centers across Maryland completed the Comprehensive Feeding Practices Questionnaire (CFPQ) and provided demographic information and perceptions of their child's size and temperament. Exploratory Factor Analysis of CFPQ identified 13 factors, and latent profile analysis (LPA) empirically identified three FP classes. Using multinomial structural equation models, we regressed FP classes on child sex, race, age, poverty level, food insecurity education, caregiver perception of child size and temperament. The most common FP pattern (69%) reflected high coercive and control with low autonomy and structural practices (Controlling Class). A second pattern (16%) had high coercive control with moderate structural and autonomy practices (Regulating Class). The third pattern (15%) reflected moderate levels of all practices (Balancing Class). Caregivers who desired their child to be heavier (aOR = 0.40, 95% CI = 0.22–0.72), were more financially secure (aOR = 0.80, 95%CI = 0.65–0.98), and were single (aOR = 0.38, 95% CI = 0.18–0.80) were less likely to be in the Balancing versus Controlling class. For each unit increase in child temperament t-score [higher = difficult], caregivers were more likely to be in the Balancing (aOR = 1.04, 95% CI = 1.01–1.07) or Regulating class (aOR = 1.04, 95% CI = 1.01–1.08) compared to the Controlling class. In this statewide sample, many caregivers endorsed controlling behaviors without endorsing empowering behaviors to help children become healthy eaters. Future studies should examine how caregiver feeding practices evolve and relate to children's eating habits, growth, and development over time.